Indian Cotton for Cairo: The Royal Ontario Museum's Gujarati Textiles and the Early Western Indian Ocean Trade. (2nd January 2017) - Barnes, Ruth
Abstract : The fragments of 'printed' cottons made in Gujarat, India, that have been discovered in deposits in Egypt provide some of the earliest and best material traces of medieval trade in the western Indian Ocean world. The article introduces an unpublished collection of thirty-four such Indo-Egyptian textile fragments now in the Royal Ontario Museum in Toronto. It discusses their likely provenance and establishes their functions, probable age, production techniques, iconography and stylistic traits through a comparison to similar fragments held in other museum collections in North America and Europe, especially the extensive Newberry collection of the Ashmolean Museum. The fragments can thus be identified as the remnants of clothing and furnishing, classic representatives of Indian printed cotton traded to Egypt during the Fatimid, Ayyubid and Mamluk periods (tenth to early sixteenth centuries). They include examples of the three major technical categories (resist-printed or -painted, mordant-printed or -painted, or both) and pseudo-Arabic script. This so far neglected material is further interpreted and contextualised within the framework of recent studies on the densely intertwined medieval trades of Egypt, India and the wider Indian Ocean, which saw similar Gujarati printed cottons traded as far east as Indonesia.